Fixed point results for alpha-implicit contractions with application to integral equations - Hussain, Nawab; Vetro, Calogero; Vetro, Francesca (Nonlinear Analysis: Modelling and Control, 2016)
Recently, Aydi et al. [On fixed point results for α-implicit contractions in quasi-metric spaces and consequences, Nonlinear Anal. Model. Control, 21(1):40–56, 2016] proved some fixed point results involving α-implicit contractive conditions in quasi-b-metric spaces. In this paper we extend and improve these results and derive some new fixed point theorems for implicit contractions in ordered quasi-b-metric spaces. Moreover, some examples and an application to integral equations are given here to illustrate the usability of the obtained results.